The field effect in Barrett’s esophagus: can we use it for screening and surveillance? - Farnham, Garry G. S.; Jankowski, Janusz A. (Endoscopy, 2013)
Esophageal adenocarcinoma (EAC) is a relatively uncommon but serious cancer afflicting 5 – 15 /100000 population in the UK, and in which diagnosis at the late rather than the early stage decreases the 5-year survival rates from 90 % to between 10 % and 20 % 1. Barrett’s esophagus is present as a premalignant lesion in the majority of cases of EAC and although Barrett’s esophagus is a major risk factor, only 2.5 % – 5 % of cases progress to EAC. The increased risk generally initiates a program of endoscopic surveillance that enables early intervention if the disease progresses 2.